PENGARUH KEBIJAKAN DEVIDEN TERHADAP LABA SATU TAHUN KE DEPAN - Temy Setiawan (Media Riset Akuntansi, Auditing & Informasi, 2016)
Earning growth is one of the company’s goals in accounting report. Dividend payment is assumed to have a link in the change of the profit in the following year. Pecking Order Theory revealed that a change in dividend will give a negative impact towards profit change. However, this statement contradicts to Zhou and Rulland’s research (2006) which showed that dividend payout has a positive impact towards profit change in the following year. This research is in accordance with signaling theory which describes that dividend is a reflection of a good performance from the company, thus, it will invite investors to increase their investment share. With the increase in the investment, the company is expected to expand and increase its profit.The research is conducted in Indonesia towards all emitents in the manufactory sub sector by taking 95 research samples from companies that paid dividend in 2007, 2008,2009, and 2010. The research type is quantitative research with double regression analysis instrument. The dependent variable is the change of profit while the independent variable is dividend payout. Variable controls in this research are ROA, leverage, and size.The result of the research shows that dividend payout does not significantly influence the change of profit even though the number of co-efficient regression is positive. ROA and leverage variables significantly influence the change of profit while Size variable does not significantly influence it. In the maturity and stable level, the company will find it hard to increase the profit even though dividend payment is high.Keywords: Earning growth,Profit,  ROA, Leverage and Size.